التدريب ودوره في مكافحة الجريمة المنظمة عبر الوطنية - - بن عبيد نجيب- زواوي الطاهر (المسيلة, 2022)
بغية مواكبة ما يشهده العالم من تطورات تكنولوجية في ارتكاب الجرائم المنظمة بطريقة تختلف عن الجرائم التقليدية، اتجهت السياسات الجنائية الحديثة إلى تزايد الاهتمام بتدريب العنصر البشري، فالحاجة اليوم تستدعي توافر رجال لهم دراية كاملة بمختلف أبعاد الجريمة. لأجل ذلك كان لا بد أن تكون تلك الأجهزة على مختلف أنواعها على درجة كبيرة من الكفاءة والمعرفة والقدرة على كشف غموض تلك الجرائم والتعرف على مرتكبيها بسرعة ودقة متناهيين، وهذا لن يتحقق إل بالتدريب سواء كان تدريب أمني أو قضائي. Chapter summary: In order to keep pace with the technological developments that the world is witnessing in the commission of organized crimes in a way that differs from traditional crimes, modern criminal policies have tended to increase interest in training the human element, as the need today calls for the availability of men with full knowledge of the various dimensions of crime. For this reason, it was necessary for these devices of all kinds to have a high degree of efficiency, knowledge and ability to uncover the ambiguities of these crimes and identify the perpetrators with extreme speed and accuracy, and this will only be achieved through training, whether it is security or judicial training.
Keywords: التدريب-- مكافحة الجريمة المنظمة - الوطنية